Refrigerating systems : CIBSE commissioning code R - Welch, Terry (Chartered Institution of Building Services Engineers, 2002)
Presents recommendations and guidance on current standards of good commissioning practice. Deals with the work involved in the commissioning of refrigerating plant used in air conditioning installations in buildings.
"Dti Department of Trade and Industry."
Keywords: Refrigeration and refrigerating machinery.; elektronické knihy; electronic books